Self-reported side effects after vaccination against COVID-19 in Honduras - Figueroa Avilez, Paola; Morel Santos, Salvador; Castillo Mencia, Carmen; Romero Caballero, Mauro; Salgado Ávila, Elizabeth; Regalado Elvir, Darling; Rivera Borjas, Nayely; Valladares Santos, Thania; Espinal Ordóñez, Alejandra; Madrid Baide, Wilmer; et al. (Open Science Journal, 2022)
Background: In December 2019, in the community of Wuhan, in Hubei, China, a series of atypical pneumonia cases with severe course was identified and the new disease was called COVID-19. By March 2020, the World Health Organization declared a pandemic. Understanding SARS-CoV2 genomic allowed the scientific community to develop vaccine candidates against COVID-19. Over 41 scientific groups conducted clinical trials to prove vaccines efficiency, efficacy, and safety. Method: A cross sectional retrospective study performed in Honduras since July 21st, 2021, to December 1st, 2021. This study included the population who received at least one dose of any COVID-19 vaccine. The data were collected using an online survey using Google Forms and a QR code to make it easier for the participants to access the survey and to avoid collecting any personal data from the participants. The symptoms were self-reported. A total of 2108 participants were included in the study through the online survey. Results: The average age of the participants was 34.61±11.129 years with higher frequency of people between 20-29 years old. In 60.7% of the cases, side effects were reported after the first dose of COVID-19 vaccine or in cases when only one dose was required. Only 1916 received a second dose of COVID-19 vaccine and 38.9% of them presented side effects after that second dose. The most common side effect is pain in the injection site (49.7% and 30.7%). The most common systemic side effects are fever (34.8% and 17.5%), headache (33.5% and 19.1%) and myalgia (32.8% and 17.6%). Conclusions: The side effects reported by the population after any vaccination against COVID-19 are mainly systemic effects like fever, myalgia and headache, while the most common local side effect is pain in the injection site. The rates of side effects are higher in females, and younger participants after both doses, the differences are statistically significant.